2019
DOI: 10.2174/1573399814666180903162556
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Role for Sodium Orthovanadate in the Treatment of Diabetes?

Abstract: The sodium orthovanadate could be developed as an anti-diabetic agent. However, further studies are required to confirm its safety profile in the treatment of diabetes mellitus before starting a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…V is an element having multiple possible roles in animals and human. Although toxic effects induced by high doses have been reported, many studies suggested the opportunity of exploiting V-based products as metalpharmaceuticals [ 9 ]. It is well known that metals released in the environment, in a close contact with organisms, can accumulate along the food chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V is an element having multiple possible roles in animals and human. Although toxic effects induced by high doses have been reported, many studies suggested the opportunity of exploiting V-based products as metalpharmaceuticals [ 9 ]. It is well known that metals released in the environment, in a close contact with organisms, can accumulate along the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…V compounds represent an encouraging search field in medicine as several studies have revealed the potential role of V-based products for the treatment of several pathologies (dysmetabolic syndromes, neurodegenerative diseases and heart disorders) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some preliminary studies of vanadium compounds as potential antidiabetic agents but no phase 2 trials (Rana & Kumar, 2018;Thompson & Orvig, 2006). Vanadium compounds are sold as dietary supplements.…”
Section: Sodium Orthovanadatementioning
confidence: 99%
“…Recently, V derivatives have been considered as potential therapeutic factors for several diseases (e.g., obesity, diabetes, cancer, neurodegenerative, and heart disorders) [12][13][14]. For all these reasons, many studies on V compounds were conducted to investigate their therapeutic and/or toxicological effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, many studies on V compounds were conducted to investigate their therapeutic and/or toxicological effects [15]. There is a considerable interest on Na 3 VO 4 due to its role in the treatment of diabetes [12], even if its toxic effects in terms of stress, autophagy, and apoptosis induction were recently reported [16]. The V 2 O 5 is instead used as a catalyst for the conversion of sulphur dioxide to trioxide when producing sulphuric acid and maleic anhydride, which is a chemical required to produce polyester resins and fiberglass [17].…”
Section: Introductionmentioning
confidence: 99%